The effect of injection molding processing conditions and fiber content towards the properties of polypropylene-nanoclay nanocomposites blend with gigantochloa scortechinii fibers - Khamis, Siti Zubaidah (2017)
Nowadays, plastics injection molding has been in high demand. In this study, the Taguchi method is used to obtain the optimum processing conditions. The designs that are used of injection molding L934 of the 9 trials, 3 levels, and 4 processing conditions as factors. Processing conditions selected were melt temperature, packing pressure, screw speed and filling time. At first, (GS) Gigantochloa Scortechinii has to be heated at a temperature 120 °C then mixed with polypropylene, maleic anhydride modified polypropylene oligomers (PPgMA) and nanoclay according to fixed measure. Mixing process was performed using a twin screw brabender mixer machine. Next, forms of grain were produced using Plastic Granulator machine for use in the injection moulding process. In order to obtain the data of flexural strength, shrinkage and warpage, the measurement process and flexural strength tests were done. As a result, the minimum value of warpage was 0.003 mm, shrinkage of 0.00048 mm and maximum flexural strength was 36.3390 MPa. To get the best results for flexural strength, the highest value while for warpage and shrinkage, the lower is the best value. For ANOVA analysis, the quality of the highest percentage indicated the parameters that produce the best specimens. In conclusion, the objective of this study has been achieved with parameters that influenced the warpage, shrinkage, and flexural strength. Besides that, in the composition of GS would influence the percentage of injection moulding with setting for the warpage A1B3C3D1, shrinkage A2B1C1D3 and flexural strength A1B2C2D2.